KONSEP KEPEMIMPINAN PENDIDIKAN DALAM MENGEMBANGKAN PRINSIP PEMBERDAYAAN MASYARAKAT - Marjuni, H.A. (Universitas Islam Negeri Alauddin Makassar, 2021)
Leadership is the process of inspiring others to work hard to achieve important work. Leadership builds commitment and enthusiasm for people to carry out their talents to help achieve plans, supervision so that things go well. In its activities, the leader has the power to mobilize and influence his subordinates in relation to the tasks that must be carried out. At the assignment stage, the leader must provide clear direction and guidance, so that subordinates can carry out their duties easily and the results are achieved in accordance with the objectives that have been set. Conceptually, the term empowerment has the basic word